Psychological dynamics of oniomania behavior among university students in Zagazig (Egypt) (Case Study) - El-Tayeb, Nermeen Ahmed Abdel-Azeem (Journal of Educational and Psychological Sciences, 2021)
This research aims to reveal the psychological dynamics of the behavior of oniomania  among university students in Zagazig, Egypt. In order to achieve this goal, the clinical method was used and by applying tests and TAT and D.A.F test on two cases. The results concluded that the high status of the anomalistic behavior suffers from very high narcissism, inflated self-image, and has a very high superego. As for the second case, low on the behavior of oniomania, it was found through the application of the test that he suffers from repression of advice, Oedipus complex disorder and focus on the mother, suffers from depression and loss of relationship with the environment, suffers from a struggle of the feet of sizes, and suffers from a narcissistic wound. As for the A.F.D test, the high status oniomania Behavior suffers from an Oedipus complex, suffers from overemphasis and this was confirmed and appeared in the interpretation of the Tat test, she needs security, suffers from an inflated self-concept and very high narcissism in asserting her drawing for herself without the rest of the family members.The shading indicates anxiety and the presence of conflicts between the body’s instinctive impulses and mental control, suffering from difficulties in sensory expression. As for the second low case, the results showed that it suffers from fixation on the mother, helplessness and lack of control and control in the environment, suffers from overemphasis in the form of control and emotional control Independence and lack of reliability, inefficiency because his drawings appear small in size, his use of shading is evidence of anxiety or fixation and this is what became clear in the Tat test, and the installation appeared in the A.F.Dand its fixation on the mother after applying the psychometric test of oniomania behavior prepared by the researcher, and based on these results the researcher recommends counseling programs in this field and psychological edification.
Keywords: Oniomania behavior; university students in Egypt; psychologic dynamic; TAT test; DAF test